Phonological awareness and emerging reading skills of two- to five-year-old children. Issue 11 (1st November 2016) - Suortti, Outi; Lipponen, Lasse
ABSTRACT: This study, conducted in Finnish private and Montessori child care centres, aimed at investigating the development of the phonological awareness (PA) of two- to five-year-old preschool children within a six-month period in relation to emerging letter knowledge and reading skills. The children ( N = 72) performed five phonological tasks and a vocabulary test, a letter knowledge test and a reading skills test twice; in the beginning, when knowing no letters, and at the end of the study. The results show that the children's performance in the different phonological tasks improved over a six-month period. Detecting word structure or blending phonemes were easier than producing rhymes or twisting. The children who had learned to recognize letters performed better in phonological tasks than the children who had not learned any letters, but children able to read precociously exceeded all. Our results appear to indicate that learning letters does not require previous PA ability but affects PA.